The Wall Street crash, 29th October 1929 - Woolf, Alex. (London : Hodder Children's Books, 2002)
Describes the stock market crash of October, 1929, and provides an overview of events leading to "Black Tuesday," as well its effects on families, the economy, and world politics.
Includes index.
Keywords: New York Stock Exchange -- 1929 -- History; Stock Market crash -- United State -- 1929.; United States -- Economic conditions -- 1918-1945.